Quantificação de carga interna de treinamento e marcadores fisiológicos em atletas de Goalball - Pastório, Juliana Jacques (2013)
Internal load can vary between training athletes, according to the perception training. The relationship between training load and physiological markers and changes in athletes goalball not yet been studied. The study aimed to quantify internal load training for the visually impaired and analyze respectively the physiological demands of the sport training in Goalball. 9 subjects in Article 1 and Article 2 in 5 subjects who underwent a medical history and collections training. The loads were quantified by the methods of PSE session) and EdwardsTL collections of blood and saliva performed to analyze cortisol and salivary osmolality, total protein (preand post), blood lactate (pre, post 3:07 minutes) IL-6 and TNF- (pre and post 30 minutes). Descriptive statistics were performed, tested the data normality by the Shapiro-Wilk test and homogeneity by Leveane. Used repeated measures ANOVA and Friedman, Student teste t, Wilcoxon test, Pearson correlation, Spearman, and Bland-Altman. Significance taken at p <0.05. For cortisol, salivary osmolality and total protein was no significant difference between pre and post. The average values of lactate found for the pre, post and 3 and 7 minutes were : 1,56 mmol.L-1± 0,88; 3,30 mmol.L-1 ± 1,3); 3,18 mmol.L-1 ± 1,62; 2,88 mmol.L-1 ± 1,51. Regarding IL6 and TNF-values found were more senior post workout: 29,40 pg/ml (23,40 -51,20) e 7,5 pg/ml (6,2 -10,50) respectively. The correlation between IL-6 and TNF- and total proteinshowed strong. The PSE session was quantified at 242.65 (± 46.03) AU Blood lactate showed peak values in practice 1 (3,49±1,10 mmol.L1); 2 (3,83±1,08 mmol.L1) e 3(3,21±0,61 mmol.L1). The method of EDWARDSTL values found for training 1, 2 and 3 were respectively: UA 166.1 (± 16.1) 165.8 AU (± 30.5) and UA 163.2 (± 18.1). Through the method of PSE were in training session 1: 273.6 ± 64.9 U.A, workout 2: 215.1 ± 45 U.A, workout 3: 234.4 ± 77.1 U.A. Correlations were found between PSE and training in TRIMP 1 (r = 0.63) and 3 (r = 0.76) and poor agreement between methods. The practice of sport Goalball analyzed were characterized with high intensity and monotony and low median and low lactate values. Quantification methods of training loads and showed strong average correlation among themselves, being capable of quantifying training loads effectively in the sport Goalball but showed poor agreement among themselves. This can also be observed in the blood and salivary variables analyzed. Thus it is necessary to quantify training loads and physiological variables in play so you can fit loads of training demands of the sport.